Taphonomic analysis of an articulated mysticete (Cetacea; Mysticeti) from the late Miocene Puerto Madryn Formation, Península Valdés, Patagonia, Argentina - Farroni, Nicolás Daniel (2021)
Taphonomic studies of fossil cetaceans in Argentina are scarce and they were focused mainly in odontocetes and misticetes from the Gaiman Formation (lower Miocene of Patagonia).These analyses propose different factors (i.e., paleoenvironmental, paleobiological andpaleoecological) that controlled the preservation of cetaceans. Prospecting fieldworks on the Puerto Madryn Formation (late Miocene) result in the discovery of a well-preserved and articulated baleen whale (= Mysticeti) specimen in Peninsula Valdés, Chubut, Argentina. This specimen was the focus of a taphonomic analysis with a multidisciplinary approach including taxonomical, sedimentological, stratigraphic and ichnological analyses, with the aim of reconstructing the taphonomic processes and the paleoenvironmental conditions that played a role in the preservation of the specimen. The preliminary taxonomic analysis shows that the specimen corresponds to an adult to subadult belonging to the family Balaenidae.